2011
DOI: 10.1242/jeb.043638
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal signal variation in space and time: how important is matching a signal with its signaler?

Abstract: SUMMARY Multimodal signals (acoustic+visual) are known to be used by many anuran amphibians during courtship displays. The relative degree to which each signal component influences female mate choice, however, remains poorly understood. In this study we used a robotic frog with an inflating vocal sac and acoustic playbacks to document responses of female túngara frogs to unimodal signal components (acoustic and visual). We then tested female responses to a synchronous multimodal signal. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 45 publications
2
64
0
Order By: Relevance
“…In fact, other studies have shown that in order for fish to respond behaviourally to conspecific sounds, they must be pre-exposed to other sensory modalities involved in courtship (Lugli, 1997;Lugli et al, 2004). In contrast, a set of elegant playback experiments that used robotic frogs to test cross-modal and multimodal communication in anurans has shown that temporally asynchronous visual and acoustic signals failed to elicit the appropriate behavioural responses in both the agonistic and mating contexts, although the degree of failure depended on the level of temporal displacement (Narins et al, 2005;Taylor et al, 2011). In the Túngara frog, Physalaemus pustulosus, for example, the visual cue of the vocal sac inflation that accompanies vocalizations is neither necessary nor sufficient for mate attraction as it does not elicit female attraction when presented alone nor does it enhance female preference when it accompanies a mating call (Taylor et al, 2011).…”
Section: Acoustic and Visual Courtship Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, other studies have shown that in order for fish to respond behaviourally to conspecific sounds, they must be pre-exposed to other sensory modalities involved in courtship (Lugli, 1997;Lugli et al, 2004). In contrast, a set of elegant playback experiments that used robotic frogs to test cross-modal and multimodal communication in anurans has shown that temporally asynchronous visual and acoustic signals failed to elicit the appropriate behavioural responses in both the agonistic and mating contexts, although the degree of failure depended on the level of temporal displacement (Narins et al, 2005;Taylor et al, 2011). In the Túngara frog, Physalaemus pustulosus, for example, the visual cue of the vocal sac inflation that accompanies vocalizations is neither necessary nor sufficient for mate attraction as it does not elicit female attraction when presented alone nor does it enhance female preference when it accompanies a mating call (Taylor et al, 2011).…”
Section: Acoustic and Visual Courtship Signalsmentioning
confidence: 99%
“…In contrast, a set of elegant playback experiments that used robotic frogs to test cross-modal and multimodal communication in anurans has shown that temporally asynchronous visual and acoustic signals failed to elicit the appropriate behavioural responses in both the agonistic and mating contexts, although the degree of failure depended on the level of temporal displacement (Narins et al, 2005;Taylor et al, 2011). In the Túngara frog, Physalaemus pustulosus, for example, the visual cue of the vocal sac inflation that accompanies vocalizations is neither necessary nor sufficient for mate attraction as it does not elicit female attraction when presented alone nor does it enhance female preference when it accompanies a mating call (Taylor et al, 2011). However, matching the visual (inflation of the vocal sac) and the acoustic signals may still play a role in modulating mate choice because Túngara frog females strongly discriminate against asynchronous multimodal signals in favour of the male call alone (Taylor et al, 2011).…”
Section: Acoustic and Visual Courtship Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of lowlevel temporal redundancies when processing vocal signals appears to be a relatively primitive evolutionary trait in vertebrates. Indeed, the temporal synchronisation of male advertisement vocalisations and air sac inflation influences female mate choice in anuran amphibians (Taylor et al, 2011). Mammals generally broadcast loud vocalisations orally (e.g., dog barks or goat bleats) (Fitch, 2000a), which means that the acoustic signal is usually accompanied by spatially and temporally corresponding facial movements as the signaller opens and closes their mouth.…”
Section: Spatio-temporal Correspondencesmentioning
confidence: 99%
“…In the final section, we show that a wide range of mammalian species appear to develop multisensory cognitive representations about signals and signallers, enabling them to form time-independent expectations about the multisensory composition of communicative stimulus features (see Table 1 for a synthesis of studies). luminance and auditory pitch (Ludwig et al, 2011) conspecific call types (Izumi and Kojima, 2004;Parr, 2004) conspecific identities (Kojima et al, 2003;Martinez and Matsuzawa, 2009) old-world monkeys rhesus macaque (Macaca mulatta) conspecific call types (Ghazanfar and Logothetis, 2003) number of conspecific signallers (Jordan et al, 2005) looming/approaching signals (Maier et al, 2004;Ghazanfar and Maier, 2009) conspecific body size (Ghazanfar et al, 2007) conspecific identities (Adachi and Hampton, 2011;Sliwa et al, 2011) heterospecific identities (Sliwa et al, 2011) Japanese macaque (Macaca fuscata) species (both their own species and humans) (Adachi et al, 2006, Adachi et al, 2009 vervet monkey (Chlorocebus pygerythrus) heterospecific call types (Zangenehpour et al, 2009) grey cheeked mangabey (Lophocebus albigena) conspecific identities (Bovet and Deputte, 2009) new world monkeys tufted capuchin (Cebus apella) conspecific call type (Evans et al, 2005) squirrel monkey (Simia sciureus) heterospecific identities lemurs ring-tailed lemur (Lemur catta) conspecific identities (Kulachi et al, 2014) Carnivora domestic dog (Canis familiaris) conspecific body size (Faragó et al, 2010;Taylor et al, 2011) heterospecific identities heterospecific gender (Ratcliffe et al, 2014) Perissodactyla Domestic horse (Equus caballus) conspecific identities (Proops et al, 2009) heterospecific identities McComb, 2012) al., 1996;…”
Section: Introductionmentioning
confidence: 99%